Genetic predisposition to neurodegenerative diseases and risk of stroke: A Mendelian randomization study - Li, Fuju; Wang, Yunyun; Hou, Xiaoyan; Cao, Lina; Zhou, Xiaoyi; Yuan, Weiyan; Shen, Yi; Tian, Tian (Frontiers in Neuroscience, 2022)
Background: Traditional epidemiological studies suggested that Neurodegenerative diseases (ND) might correlate with stroke. We intend to explore whether the two most common neurodegenerative diseases [Alzheimer's disease (AD) and Parkinson's disease (PD)] are causally associated with stroke and its subtypes. Methods: Two-sample Mendelian Randomization (MR) method was used to explore the causal relationships. Candidate genetic instrumental variables (IVs) for AD and PD were collected from the genome-wide association studies (GWAS) in European populations. The inverse-variance weighted (IVW) method was the primary method of MR analysis, and the weighted median method was supplementary. In addition, the MR-Egger method and the MR-PRESSO test were used as well. Results: We found no causal effects of AD on stroke, Ischemic stroke (IS), or Intracerebral hemorrhage (ICH). As for PD and stroke, our preliminary results showed PD could causally influence the risk of stroke (odds ratio [OR]: 1.04; 95% confidence interval [CI]: 1.02-1.07; P = 0.001 by the IVW method), although the alternative method did not support this result. We identified the positive causal relationship between PD and the risk of IS (OR = 1.04; 95% CI: 1.02-1.07; P = 0.001 by the IVW method), and the alternative MR methods produced similar results. The present study found there was no causal relationship between PD and ICH. Conclusion: This study found a causal relationship between genetic susceptibility to PD and the incidence of stroke (especially IS) in the European population; however, there was no causal relation between AD and stroke risk.